Van der Woude syndrome- a syndromic form of orofacial clefting - Sudhakara Reddy, R. (Medicina Oral S.L., 2012)
Van der Woude Syndrome is the most common form of syndromic orofacial clefting, accounting for 2% of all cases, and has the phenotype that most closely resembles the more common non-syndromic forms. The syndrome has an autosomal dominant hereditary pattern with variable expressivity and a high degree of penetrance with cardinal clinical features of lip pits with a cleft lip, cleft palate, or both. This case report describes van der Woude syndrome in a 19 year old male patient with a specific reference to the various aspects of this condition, as clinical appearance, etiological factors (genetic aspects), differential diagnosis, investigative procedures and management. Key words:Cleft palate, cleft lip, lip pits, van der Woude syndrome, syndromic clefting.